Tingkat Prokrastinasi Akademik Siswa Kelas XI SMA Negeri 11 Semarang - Muhammad Irham Fazlurrahman; Siti Fitriana; Andarini Bhakti Sativa (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
This study aims to portray the academic procrastination behavior experienced by the 11th grade students of SMA N 11 Semarang. The results of the identification are expected to describe the level of academic procrastination of students in class XI SMA N 11 Semarang. This research was conducted using a descriptive quantitative type that will produce a complete description of the research results. This research approach aims to describe the level of academic procrastination of students, the population of the study is the XI grade students of SMA N 11 Semarang totaling 96 students. The sample collection technique in this study is simple random sampling technique. "Simple random sampling technique" is a simple technique because taking sample members from the population is done randomly without seeing and paying attention to the equality or strata that exist in the population". The results of calculating the academic procrastination scale score with a study subject of 96 students in class XI SMA Negeri 11 Semarang. Researchers found that students who entered the very low classification amounted to 0 with a percentage of 0%, in the low classification there were 14 students with a percentage of 38.5%, in the medium classification there were 45 students with a percentage of 46.9%, in the high classification there were 37 students with a percentage of 14.6%.